BLOOD PRESSURE REDUCTION ON ELDERLY WITH HYPERTENSION WITH CELERY PRODUCTS IN PEKALONGAN CITY - Ni'matul Ulya; Miftachul Jannah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
Elderly is an ageing process where age reaches more than 60 years. Hypertension is a state of increased systolic blood pressure more than equal to 140 mmHg and 90 mmHg for diastolic on two measurements with an interval of five minutes in a state of sufficient rest/calm. The study purpose was to determine the effectiveness of celery products on the reduction of blood pressure in the elderly with hypertension. Design of this study was quasi-experimental. The population of this study was elderly with hypertension; the sample was taken using a multistage random sampling technique and obtained 15 people per group. The results showed that the characteristics of respondents based on gender were mostly female was 22 respondents (73.3%). While the characteristics of respondents based on age were mostly between the ages of 60 - 65 years were 16 respondents (53.3%). The results of systolic blood pressure measurement in elderly hypertension given celery leaf extract were higher at an average of 28.33 mmHg compared to those given simplicia of celery leaf, which was an average of 22.67 mmHg. The results of measurements of diastolic blood pressure reduction respondents who were given celery leaf extract were higher at an average of 18 mmHg compared to those given simplicia of celery leaf, which was on average 12.3 mmHg. There are differences in the average pre and post diastolic pressure in elderly with hypertension who were given simplicia and celery leaf extract. There is no difference in systolic and diastolic blood pressure reduction between those given simplicia and celery leaf extract. Keywords: Elderly, Hypertension, Celery